Gluten-free extruded products: a review - Paykary, Maryam; Karim, Roselina; Aghazadeh, M.; Kazemi, M. (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Although, gluten is one of the most important components in cereal technology, due to the claim that almost 0.05% of the current world population has allergy to gluten (celiac patients), there is a growing necessity to increase the choices of gluten free products. Extruder as a versatile and highly efficient instrument for thermal and mechanical processing has a widespread application in food production. Also because of its versatility, it is a high efficient instrument in food industries. While there is a new approach to prepare gluten free products, the varieties of them are not comparable to the needs of demanded people. This review discusses on production of gluten free food products using extruder. High starch, high protein, and high fiber gluten free food products and their physical, chemical, rheological and sensory properties were compared to that of gluten based material. Different kinds of seed flour and their starches (rice, pigeon pea, buckwheat, soy bean, kidney bean, amaranth, cassava, oat, sorghum, and quinoa) have been used as improving agents. The effect of extrusion at appropriate conditions (type of extruder, barrel temperatures, screw speeds, die-nozzle rate, and feed rate), with or without addition of other ingredients on the physical and chemical characteristics of the new products were discussed. In many cases, improvers were significantly (p<0.05) useful to retain the gluten benefits in the final products that were developed, even were able to act exactly as gluten in material matrix.